Implementation of Evidence-Based Nursing: The Effect of Foot Massage Therapy on Reducing Blood Pressure in Hypertension Patients - Wahyu Utami, Rizka; Rahayu, Fitri; Widi Widowati, Arinta (Jurnal Riset Media Keperawatan, 2025)
Hypertension is a non-communicable disease (NCD) associated with unhealthy lifestyle behaviors and often occurs without noticeable signs or symptoms; therefore, it is known as a silent killer. Blood pressure control is essential to prevent complications, and effective management strategies are required, including complementary therapies. Foot massage is a non-pharmacological intervention that has the potential to reduce blood pressure. This study aimed to determine the effect of foot massage therapy on blood pressure reduction in patients with hypertension. This study employed a quasi-experimental design with a sample of 22 respondents. The results showed that before the foot massage intervention, the mean systolic and diastolic blood pressure of respondents was 160.8/92.2 mmHg, while after the intervention, it decreased to 145.5/85 mmHg. Data were analyzed using the Wilcoxon test. The findings indicated that foot massage therapy had a significant effect on reducing blood pressure in patients with hypertension, with a p-value of 0.001. This study recommends foot massage as an evidence-based nursing intervention that can be independently implemented by nurses as a complementary non-pharmacological therapy to assist in blood pressure control among patients with hypertension.